Peran Kesadaran Merek, Citra Merek, dan Keaslian Merek Terhadap Keputusan Pembelian Produk Kosmetik Halal BB Cream pada Konsumen Wardah di Kota Semarang Berbasis Kuisioner Online - Adelia Nirmala Cahya; Amron Amron; Vincent Didiek Wiet Aryanto; Ariati Anomsari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research evaluated the impact of brand awareness, image, and authenticity on Wardah BB Cream purchasing decisions among 150 consumers. Using a quantitative approach and PLS-SEM analysis, the study results showed that all three factors made a significant positive contribution. Among the three, brand authenticity was found to be the most dominant factor driving consumers to make a purchase. These findings indicate that strengthening authenticity values ​​and consistent brand image play a crucial role in driving purchasing decisions for halal cosmetic products.